Antral pseudocysts of the maxillary sinus: relationship between radiographic and clinical features - Rodrigues, Cleomar Donizeth; Arruda, José Alcides Almeida de; Silva, Luciano Barreto; Guimaraes, Carolina dos Santos; Sobra, Ana Paula Veras; Silveira, Marcia Maria Fonseca da; Estrela, Carlos (Journal of Oral Diagnosis, 2017)
Antral pseudocysts of the maxillary sinus are the second most common lesions in the maxillary sinus region. The aim of this study was to analyze the frequency of antral pseudocysts of the maxillary sinus diagnosed with panoramic radiographs, cone beam computed tomography and a clinical questionnaire. This was a cross-sectional study in- volving patients of a private radiology institute. A total of 185 panoramic radiographs with images suggestive of antral pseudocysts were selected out of 6,000. The patients were invited to attend the service and 28 were selected for this study. Panoramic radio- graphs were obtained and, when the image was suggestive of antral pseudocysts, the patient was invited to undergo cone beam computed tomography and to answer a clinical questionnaire. The control group consisted of 30 patients without antral pseudocysts on panoramic radiographs who had undergone cone beam computed tomography and who had filled out the clinical questionnaire. Pearson’s chi-square test and Fisher’s exact test were used to determine differences in the frequency of the variables among study groups, adopting a p value of 0.05 and a 95% confidence interval. The relationship between cone beam computed tomography and the diagnosis of antral pseudocysts, and with the data collected with the clinical questionnaire was established. A statistically significant difference was found regarding atrophy of the turbinates and obstruction of the meatal ostium. In addition, patients with antral pseudocysts had significantly more histories of allergy, allergy persistence, and use of topical nasal medication compared to the control group, as well as nasal obstruction, thick nasal discharge, a runny nose and postnasal drip. The use of topical nasal medication and the presence of atrophy of the turbinates and obstruction of the meatal ostium suggest a relationship with the occurrence and persistence of antral pseudocysts.